Fully Substituted Dihydropyrimidines, Pentasubstituted 2-Aryldihydropyrimidines Synthesized by Palladium-Catalyzed/Copper-Mediated Cross-Coupling Reaction - Nishimura, Yoshio; Kubo, Takanori; Shibuya, Nanami; Cho, Hidetsura (Synthesis, 2023)
Dihydropyrimidines (DPs) show a wide range of biological activities suitable for medicinal applications. Among DP derivatives, 2-aryl-DPs have been reported to display remarkable pharmacological properties. In this work, a method of synthesizing hitherto unavailable fully substituted pentasubstituted 2-aryl-DPs as tautomeric mixture is described using a Pd(PPh3)4-catalyzed/CuBr-mediated 2-arylation reaction. The reaction using aryltributylstannanes with various substituents such as MeO, Me, Ph, CF3, CO2Me, and NO2 groups efficiently afforded the corresponding 2-aryl-DPs in high yields. Heteroaryltributylstannanes having 2-thienyl, 3-thienyl, or 2-pyridinyl groups were also suitable for the reaction. Regarding the substituents at the 4-, 5-, and 6-positions of DPs, the reactions of DPs bearing substituents such as Me, n-C3H7, n-C5H11, -(CH2)5-, phenyl, and fluorenylidene groups proceeded smoothly to give the desired products. The synthetic method was also applied to a 2-thioxo-DP to give the 2-aryl-DP. Therefore, the reaction will help expand DP-based molecular diversity, which may impact biological and pharmacological studies.
Keywords: dihydropyrimidine; fully substituted 2-aryldihydropyrimidine; Pd-catalyzed/Cu-mediated reaction; Liebeskind–Srogl-type cross-coupling reaction; palladium catalyst; copper reagent; aryltributylstannanes; heteroaryltributylstannanes